ENHANCING FINANCIAL LITERACY TO PROMOTE FINTECH ADOPTION AND MSME PERFORMANCE - Putra, Gilang Kharisma; Khafid, Abdul; Hastuti, Erma Sri (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the impact of financial literacy on the adoption of fintech in improving the performance of SMEs in Kendal Regency through the Technology Acceptance Model (TAM). The fundamental issue that is difficult to avoid for MSME actors in Indonesia regarding financial management is the limited understanding of access to financial services, especially from formal financial institutions. This is due to the still low level of financial literacy. MSME actors play a crucial role in national economic development, but their growth is constrained by this lack of financial knowledge. Using a causality approach with the aim of developing predictions and strategies to improve financial literacy in promoting the adoption of fintech and the performance of SMEs in Kendal Regency through the Theory of Acceptance Model. The research data consists of primary data obtained directly from questionnaires distributed via Google Forms. The population of this study includes SMEs in Kendal Regency that are already using fintech, with the sampling technique employing purposive sampling methods. From the five hypotheses proposed, the statistical results indicate that four hypotheses were accepted because they meet the criteria. Meanwhile, one hypothesis was rejected because it did not meet the specified criteria. This research outcome assists local government in designing strategies to enhance financial literacy and fintech service utilization among MSMEs, thus improving sustainable business performance.